PENYULUHAN TENTANG PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA WANITA USIA SUBUR - Yunita Anggriani; Komalasari Komalasari; Maulia Isnaini Isnaini; Rika Agustina; Nopi Anggista Putri; Mareza Yolanda Umar; Juwita Desri Ayu; Psiari Kusuma Wardani; Elsy Juni Andri Karini (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2024)
Long Term Contraceptive Method (MKJP) is a contraceptive method that works for a long time and has high effectiveness in preventing pregnancy. The use of contraception is one of the effective efforts in the Family Planning Program to control fertility or suppress population growth. In its implementation, efforts are made to ensure that all contraceptive methods or devices provided or offered to the public provide optimal benefits. In choosing a method, a woman must consider various factors, including health factors, potential side effects of a method, and the consequences of unwanted pregnancy. However, contraceptive use among women at young and old ages (risk age) is much lower than for women aged 20-39 years (non-risk age). Family Planning (KB) participants are women of childbearing age (WUS), one of whom uses contraceptive methods/methods for the purpose of preventing pregnancy or better known as acceptors. This community service implementation was carried out in Kediri Village Gading Rejo Districtand followed by 25 women of childbearing age. The methods used in health education are lecture, discussion and question and answer methods using flip sheets. It can be concluded that the education day regarding the use of MKJP can increase awareness and interest among women of childbearing age to choose to use long-term contraceptive methods and understand the many benefits of using long-term contraceptive methods.